Developing recommendations for implementing the Australian Pain Society's pain management strategies in residential aged care - McConigley, Ruth; Toye, C.; Goucke, R.; Kristjanson, Linda (Wiley-Blackwell Publishing, 2008)
OBJECTIVE: This study aimed to develop recommendations and a related implementation resource 'toolkit' to facilitate implementation of pain management strategies in Australian Residential Aged Care Facilities (RACFs). METHODS: This qualitative study used written materials, focus groups and individual interviews to gather data from participants. Thirty-four health-care professionals with experience in the aged care sector were recruited from five Western Australian RACFs. General practitioners who had an interest in aged care were contacted via local general practice networks. RESULTS: Findings indicated that focused education sessions were needed to support implementation. A tailored toolkit was developed to assist the process. Funding and workforce constraints were found to be threats to complete implementation in some facilities. CONCLUSIONS: A multifaceted approach is needed to promote the implementation of pain management strategies in RACFs. In particular, unlicensed care workers, who may have responsibility for recognising and reporting signs of pain, require further education to support their role in the pain management process.